FACTORS INFLUENCING STUDENT’S INTEREST IN INVESTING IN SHARIA STOCK IN THE SHARIA BUSINESS MANAGEMENT STUDY PROGRAM - Shiddiqi, Syehnaz Sahin; Rahma, Sabila; Prananda, Yoga; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
Research purposes This For know influencing factors interest student in invest sharia shares. Approach research used use approach quantitative. Samples used amount three twenty people representing students all over population. Research data collection done with use distributed questionnaires with Quota sampling technique. In analyzing research data use data analysis with steps as following data quality test , assumption test classic , multiple linear regression test and testing hypothesis . With use tool help form SPSS Statistics application as data processing. Research result shows that the calculated F value is 7.946 and the F table is 3.23, which shows that the calculated F F table uses a significant value of 0.002 0.05. So in the simultaneous test (f test) it can be seen that risk and understanding have a significant and influential effect on student interest in investing in Sharia shares.